2017
DOI: 10.1371/journal.pone.0171512
|View full text |Cite
|
Sign up to set email alerts
|

Deep-proteome mapping of WM-266-4 human metastatic melanoma cells: From oncogenic addiction to druggable targets

Abstract: Cutaneous melanoma is a malignant tumor of skin melanocytes that are pigment-producing cells located in the basal layer (stratum basale) of epidermis. Accumulation of genetic mutations within their oncogenes or tumor-suppressor genes compels melanocytes to aberrant proliferation and spread to distant organs of the body, thereby resulting in severe and/or lethal malignancy. Metastatic melanoma’s heavy mutational load, molecular heterogeneity and resistance to therapy necessitate the development of novel biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 150 publications
(192 reference statements)
0
59
0
Order By: Relevance
“…Cutaneous (skin) melanoma is one of the most aggressive and treatment-resistant human cancers [ 1 ]. Indeed, skin melanoma is characterized by a high tendency to metastasize since it is located in the basal layer of the epidermis, which is constituted by several blood and lymphatic vessels [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous (skin) melanoma is one of the most aggressive and treatment-resistant human cancers [ 1 ]. Indeed, skin melanoma is characterized by a high tendency to metastasize since it is located in the basal layer of the epidermis, which is constituted by several blood and lymphatic vessels [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although NDRG-1 was downregulated in melanoma compared to in nevus, we could not detect any difference between H-scores of primary and metastatic melanomas in tissue samples. It has been shown that NDRG-1 was downregulated in majority of cancers and acts as a metastasis suppressor protein in at least a group of human carcinomas (46,47,48). The importance of NDRG-1 in melanoma is not well known; strong NDRG-1 staining was seen in melanoma samples compared to in nevus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, (1) Osteopontin acts as a cytokine and is involved in type I immune responses. Osteopontin-dependent autocrine/paracrine signaling pathways are associated with metastatic melanoma [24], and the protein is involved in cell signaling that regulates tumor progression and metastasis [25]. (2) Carbonic anhydrase 1 participates in interleukin 12-mediated signaling pathways, while Carbonic anhydrase IX inhibitors can increase the sensitivity to chemotherapy and promote the apoptosis of melanoma cells [26].…”
Section: B16 Melanoma-bearing Micementioning
confidence: 99%